2013
DOI: 10.1007/s11999-012-2700-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Flexion Measurement From Lateral Projection Radiographs is Clinically Reliable

Abstract: Our data suggest measurement of pelvic flexion angle using lateral radiographs is reliable. We recommend the measurement be performed once by two observers for better reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…However, few studies have examined the accuracy of SS. Some reports evaluated the accuracy of the pelvic flexion angle measured by manually identifying the locations of bilateral anterior superior iliac spine and the pubic symphysis by using synthesized lateral pelvic radiographs from a CT-based surgical navigation system [14,24]. They found both intra-and inter-observer error to be small and the results to be highly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined the accuracy of SS. Some reports evaluated the accuracy of the pelvic flexion angle measured by manually identifying the locations of bilateral anterior superior iliac spine and the pubic symphysis by using synthesized lateral pelvic radiographs from a CT-based surgical navigation system [14,24]. They found both intra-and inter-observer error to be small and the results to be highly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…The patient had left hip OA without hip pain. Some reports have described that in patients with advanced hip OA, external rotation of the hip joint tends to occur, and the pelvis are easy to take stoop [17]. We supposed that the patient had injured her MPFL when she fell down the stairs and landed on her left foot, during which a valgus force was applied to her left knee because her left hip leaned to compensate for the gluteus medius dysfunction, similar to that observed in Duchenne muscular dystrophy.…”
Section: Discussionmentioning
confidence: 90%
“…38 However, the tibia plafond is not flat but rather concave in shape, with an average medial angle of 22 ± 4 degrees at slight varus alignment. 1,21,25 Also, the subchondral bone plate is the cortical endplate located in the calcified region of the articular cartilage. 30 It has been demonstrated that subchondral mineralization is not homogeneously distributed across the articular surface of the distal tibia.…”
Section: Discussionmentioning
confidence: 99%
“…29 The suitability of DRRs as surrogates for standard radiographs was demonstrated in two studies. 16,21 To the best of our knowledge, DRRs have not been used to elucidate how measurements of the MDTA may be influenced by projection angle and patient positioning in the AP view and the HAV. Furthermore, the use of DRRs as a surrogate to conventional radiographs for measurement of the MDTA has not been demonstrated.…”
mentioning
confidence: 99%